Letter to Jacobsen’s Editor of Phenomena and the Management Team - May, Edwin C (Journal of Scientific Exploration, 2017)
21 April 2017 Review of Ms. Annie Jacobsen’s book Phenomena Please find attached my credentials for providing this review. I originally began to provide a line-by-line critique; however, I found that I was rewriting a book that was inaccurate, self-serving, and a legally risky example of incompetent investigative reporting. One tell-tale indication of this is the lack of fact checking and providing independent second sources. Clearly this is devastating in the intelligence community and by implication undermines all investigative reporting. Ms. Jacobsen has surrounded herself with excellent representation given the media exposure she has enjoyed. The book and this media frenzy continues to misrepresent not only the hard work and science conducted by the Star Gate team, but devalues the excellent operations carried out over the years. A few examples of the most egregious errors follow: • On page (Hardback) 492, Jacobsen claims she interviewed or otherwise corresponded with Dr. Jack Vorona, former Deputy Director of Science and Technical Intelligence for the Defense Intelligence Agency. I contacted him to verify this assertion. I was told in quite unambiguous language that he refused an interview despite Jacobsen’s continued aggression. In my view, this is not an oversight or a typo—it is, in fact, an outright lie. • Jacobsen devotes Chapter Two to “The Puharich Theory,” but he was an infrequent bystander in the very early days of the SRI program in psi research. Neither his story about drugs nor any other aspect about him was involved in the government’s effort whatsoever. The life and work of Puharich is a continuous theme throughout the book • Jacobsen devotes Chapter Six to “The Enigma of Uri Geller,” a constant theme throughout the book. Geller was involved in only a short series of experiments lasting six weeks out of a 23-year long project. This early SRI work was reported in the prestigious journal Nature—Targ, R. and Puthoff, H. E. (1974). Information transmission under conditions of sensory shielding. Nature, 252, 602–607. This landmark publication in the history of ESP research and the government’s involvement was ignored. Moreover, it is clearly stated on page 604 of the Nature paper: